Comparative performance analysis of the marina and charter service industries in Croatia - Luković, Tihomir (Array, 2021)
Marina and charter industry represent the two basic segments of nautical tourism sector, one of the key elements of tourism development in the countries of the Mediterranean circle. With the advent of ever more ambiguous business environment driven by global health hazards, the emergence of next technological revolution and global competition, insight into the antecedents of competitiveness of companies in the nautical tourism sector in an important topic for organizations who want to survive and grow. The goal of this paper is comparison of the fundamental features of these two interconnected industries. The marina industry, observed through the financial indicators, shows attractiveness and stability. Regardless of the marina category, the success of its operations proved to be stable even in crisis market conditions. On the other hand, the charter industry, that complements the value proposition of the marina industry, shows lower level of robustness in times of crisis. The contribution of the paper is twofold. Firstly, for the purpose of the comparison of these two industries we present their basic indicators, and argue that the dynamic connection of the charter and marina industries opens possibilities to achieve higher level of competitiveness in both businesses. Also, since the available data on both industries is scarce, the paper introduces a system of data estimates, as well as system of experiential forecasting which can be used in different markets where similar limitations can be observed.